ECDL Advanced Spreadsheets - Murphy, Sharon and Holden, Paul (xiii,177 Pages 24x16 cm PB)
Covers various aspects of the ECDL advanced spreadsheets module using the popular business software - the Excel package of Microsoft Office 2000. This book provides everything a student needs to pass the ECDL Advanced Spreadsheet certification test.
Include Illustrations and Index
Keywords: European Computer Driving Licence